Peran Suplementasi AREDS2 dalam Menurunkan Progresivitas Age-related Macular Degeneration: Tinjauan Pustaka - Valencia, Jessica; Pangputri, Floretta Dwinovi (PT Kalbe Farma Tbk., 2026)
Age-related macular degeneration (AMD) is a degenerative macular disease that is the leading cause of irreversible vision loss in the elderly in developed countries. The prevalence of AMD in Asian populations is 6.8% for early-stage AMD and 0.56% for late-stage AMD. Increased production of reactive oxygen species (ROS) that cannot be balanced by the retinal antioxidant system causes structural damage to the retinal pigment epithelium (RPE) layer. This damage results in RPE cell dysfunction, drusen accumulation, and disease progression to advanced stages. Antioxidant supplementation such as the AREDS2 formulation is a therapeutic option that can reduce AMD progression from intermediate to late stages. The AREDS2 formulation consists of lutein, zeaxanthin, vitamin C, vitamin E, zinc, and copper, which work through various mechanisms to protect the retina from oxidative stress, inhibit inflammation, and restore cellular function. This literature review discusses the role of AREDS2 supplementation in AMD along with the mechanism of action of each component in reducing disease progression and maintaining visual function in elderly patients.